HUKUM PIDANA DAN HAK CIPTA DI ERA KECERDASAN ARTIFISIAL: ANALISIS PERTANGGUNGJAWABAN DALAM HUKUM POSITIF DAN HUKUM ISLAM - Ruhtiani, Maya; Istikharoh (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2025)
This study examines the issue of criminal liability for copyright infringement committed through artificial intelligence (AI) from the perspective of both positive criminal law and Islamic law. The lack of a clear legal subject status for AI in Indonesian positive law creates a legal vacuum, leading to difficulties in assigning criminal liability. This research adopts a normative-juridical method with a comparative approach between positive legal norms and the principles of maqāṣid al-sharī‘ah in Islamic law. The findings reveal that Islamic law offers normative flexibility that enables accountability through the principle of property protection (ḥifẓ al-māl) and the prohibition of harm (lā ḍarar wa lā ḍirār), whereas positive law requires normative reconstruction to recognize human controllers of AI as liable actors. The study recommends the formulation of a hybrid legal norm that integrates the strengths of both systems to establish a fair and adaptive copyright protection mechanism in the digital era.